PREVALENCE OF POOR SLEEP QUALITY AMONG PATIENTS WITH TYPE 2 DIABETES MELLITUS IN PONTIANAK: A CROSS-SECTIONAL STUDY - Djoko Priyono; Ririn Afrian Sulistyawati; Sukarni; Muhammad Agung Krisdianto (Literasi Intelektual, 2025)
Background: Sleep disorders are a significant health concern among patients with type 2 diabetes. Understanding their prevalence and underlying factors is key to designing effective interventions. Methods: A descriptive cross-sectional study was conducted in 2023 involving 119 patients with type 2 diabetes aged 30–70 years at diabetic wound care and primary health clinics in Pontianak City. Data were collected using a demographic checklist and the Pittsburgh Sleep Quality Index (PSQI). Associations between sleep quality and various factors were analysed using chi-square tests and binary logistic regression. Poor sleep quality was defined as a PSQI score of 5 or higher. Results: 119 individuals (53.7 %) demonstrated poor sleep quality and had a moderate level of sleep disturbance (mean PSQI score 6.9±3.16.9±3.1), with sleep latency being the most affected domain (mean score 1.9±1.41.9±1.4). Comorbid chronic diseases (OR 2.80, p=0.001), smoking (OR 2.95, p=0.005), diabetes duration >10 years (OR 2.55, p=0.004), and obesity (BMI ≥ 30.0 kg/m²; OR 1.89, p=0.021) were significantly associated with poor sleep quality. Older age had a protective effect (OR 0.94, p=0.007). Conclusion: Sleep disorders, particularly difficulty initiating sleep, are highly prevalent among type 2 diabetes patients and associated with comorbidities, smoking, prolonged disease duration, and obesity. Interventions targeting these factors are essential to improve sleep quality and diabetes management.